Dziennik jako forma życia. Zapiski Józefa Hena. Genezy, genealogie, archiwa - Dąbrowski, Bartosz (Załącznik Kulturoznawczy, 2022)
The article discusses the impact of the experience of the Holocaust and the war on the form and issues of eight volumes of Józef Hen’s literary journals I am not Afraid of Sleepless Nights. The “long shadow” of these traumatic events shaped both the history of their delayed origins, the form of the notes, and their main themes. The poetics of these diaries is based on the structure of a collage, which, on the one hand, connects the past and present, and on the other, it combines the chronicle of everyday life with night-time meditations, memories and reflections on history, wartime and post-war experiences and the Jewish fate. Hen contrasts these devastating forces of the twentieth century with his own philosophy of life, which is a special form of Jewish vitalism. The diary thus becomes a symbolic form of survival in the form of a literary, autobiographical work. All the volumes of Hen’s journals seem to be permeated by the effort to record, preserve and perpetuate what is characterized by the fragility and susceptibility to the corrosion of time – that is, life itself. Ultimately, thanks to this effort, the trace of the author’s own presence is also preserved. The collage poetics of the record, resulting from “composing”, makes it part of the work itself. The subject is transformed in it into an idiomatic “gesture”, i.e., a trace of a constantly repeated expressive act, which seems to retain traces of the author’s expressive gestures, his preferences, choices and ways of seeing, and the modality of individual feeling recreated in the text. In a way, it can be said that, according to Hen, journals are written to preserve the specific literary composition of existence. A diary understood as a “form of life” preserves a certain inalienable ethical moment, contained both in the need to give a certain order to the biography and to save the life experience itself – in its various forms. While history and everyday life constitute a source of a constantly reborn fear in Hen’s diaries, as they seem to still emerge in the long shadow of the Holocaust and the possibility of its possible repetition recognized in many events, the very ability to transform them into a diaristic record counteracts it therapeutically. For despite the fact that life can be destroyed, thanks to writing – as Hen’s final lesson seems to sound – something can always remain and survive.